Automated Compilation Test System for Embedded System - Ishak, Mohamad Khairi; Hwan, Ooi Jun; Jiashen, Teh; Mat Isa, Nor Ashidi (Makara Journal of Technology, 2018)
Embedded system testing involves testing an integration of software and hardware. It is increasingly difficult to evaluate the functionality of each module within a short time because of the increasing number of tests required. In this paper, a novel stepwise methodology involving the use of an automated compilation test system (ACTS) is proposed, to improve the quality of testing and optimize the testing time using automation. Using the proposed method, the testing coverage can be maximized, while minimizing the manual work and testing time required. This ACTS was used to automate the test code compilation and execution for different hardware modules. The proposed method significantly saved the testing time by approximately 56.42%, compared to the existing method, while ensuring quality testing performance.